Evaluation of Split Hand Syndrome in Early Diagnosis of Amyotrophic Lateral Sclerosis by Nerve Conduction Study as a Diagnostic Tool - Wazib, Amit; Rahman, Shaila; Ahmed, Md Rayhan (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Amyotrophic lateral sclerosis (ALS), a degenerative disease of the motor neurons that can present diversly. Needle electromyography (EMG) is the gold standard investigation for the diagnosis of ALS. Split hand syndrome (SHS) demonstrated by nerve conduction study (NCS); a noninvasive tool could be useful in diagnosing ALS. This study aimed to assess SHS by NCS in ALS. Methods: This diagnostic accuracy case-control study included 37 cases of ALS and 37 age and gender-matched controls. Compound muscle action potential (CMAP) and distal motor latency (DML) of median and ulnar nerves and the ratio of median and ulnar CMAP and DML were compared between study groups. The diagnostic validity testing of electrophysiological SHS was also done. Results: The mean age of the ALS and control groups were similar, 39.8±2.7 and 39.3±2.6 years, respectively. Sixteen (43.2%) ALS patients were in 30-59 years age group. Male-female ratio was 5.2. In the ALS group, median-ulnar CMAP ratio was lower and median-ulnar DML ratio was prolonged than the control. The diagnostic efficacy of median-ulnar CMAP ratio and DML ratio were calculated. A median-ulnar CMAP ratio cut-off value ≤1 showed 70% sensitivity, 97% specificity, 96% positive predictive value and 77% negative predictive value. A median-ulnar DML ratio cut-off value ≥1.5 showed 48% sensitivity, 89% specificity, 82% positive predictive value and 65% negative predictive value. Conclusion: NCS demonstrating SHS can be an important tool in the early diagnosis of ALS. J Bangladesh Coll Phys Surg 2024; 42: 350-354